Efficacy and safety of oral minoxidil in the treatment of alopecia: a single-arm rate meta-analysis and systematic review - Liu, Chang; Liu, Xiaojie; Shi, Ting; Wang, Yun; Sui, Chaoyang; Zhang, Wenan; Wang, Bowen (Frontiers in Pharmacology, 2025)
BackgroundHair loss is a prevalent aesthetic concern that impacts the quality of life and self-image of numerous individuals. While topical minoxidil has been extensively utilized in addressing hair loss for several decades, the effectiveness and safety of oral minoxidil are still a topic of debate. Despite its use in certain clinical settings, the precise efficacy and safety of oral minoxidil have not been conclusively validated. Hence, conducting a one-arm rate meta-analysis and systematic review to assess the efficacy and safety of oral minoxidil in treating alopecia holds significant importance. This endeavor aims to furnish additional evidence to support clinical practice and offer guidance for future research in this domain.MethodsWe conducted a comprehensive search on electronic databases including PubMed, Embase, Cochrane Library, and Web of Science from their inception up to 1 October 2024. The primary objective was to assess both the efficacy (measured by the degree of symptom improvement) and safety (including adverse event incidence) of oral minoxidil in the treatment of hair loss.ResultsA total of 2,933 patients from 27 studies were included in the analysis. The efficacy of oral minoxidil for treating alopecia was primarily assessed based on the degree of symptom improvement. Among the participants, 35% (95% CI: 22%–49%) experienced significant symptom improvement, 47% (95% CI: 38%–55%) showed symptom improvement, and 26% (95% CI: 16%–37%) had stable symptoms. The incidence of adverse events in the safety evaluation was reported at 27% (95% CI: 18%–36%).ConclusionThis systematic review and meta-analysis indicate that individuals with hair loss may derive benefits from oral minoxidil, particularly at doses exceeding 1 mg. Nonetheless, additional research or data is essential to definitively establish its efficacy and safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024581183.